(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper presents a comprehensive comparative linguistic analysis of mythological units in English and Uzbek languages, examining their structural, semantic, and cultural dimensions. Drawing on contemporary research in cultural linguistics and comparative mythology, the study identifies key categories of mythological vocabulary including mythonyms, theonyms, cosmonyms, and demononyms. Through systematic analysis of etymological origins, semantic features, and cultural functions, the research reveals both universal patterns and language specific characteristics. English mythological units predominantly derive from Greek Roman and Germanic traditions, while Uzbek mythological vocabulary reflects Turkic, Persian, and Islamic influences. Both languages exhibit similar cognitive mechanisms in mythological conceptualization, demonstrating the interplay between universal cognitive constraints and cultural variation in linguistic systems.